Must know in surgery - Kadhim Jawad (Penerbit Universiti Teknologi Mara, 2010)
This book will facilitate the design of question paper, especially the MCQ type of paper. It will help the teacher setting the paper to achieve a desired balance between questions that test core knowledge, and other questions that will discriminate between students